Dramski lik in dramsko dogajanje v slovaških dramah z utopično tematiko v obdobju 1920–1948 - Lacová, Hana (Jezik in slovstvo, 2025)
The article examines the influence of the utopian and catastrophic theme on the category of character and plot, in selected dramas written in the period 1920–1948. The article introduces four dramatic work: Jozef Závodný’s (1899–1969) The Übermensch (1927), Peter Karvaš’s (1920–1999) Meteor(1945), Juraj Váh’s (1925–1976) The First and the Last Ones (1949), and Július Barč-Ivan’s (1909–1953) The End (1948). The aim of the article is to identify the key themes and artistic techniques in dramatic texts with a utopian theme through sub-categories (namely the categories of dramatic character and dramatic plot).
Keywords: 1920-1948; Barč-Ivan, Július; catastrophe; drama of ideas; dramatic characters; dramatic plot; dramski lik; dramsko dogajanje; idejna drama; Karvaš, Peter; katastrofa; Slovak dramatics; Slovak literature; slovaška dramatika; slovaška književnost; utopian theme; utopična tematika; Váh, Juraj; Závodný, Jozef